U-Prove Recommended Parameters Profile V1.1 (Revision 2) - Paquin, Christian (Microsoft, 2013)
This document defines recommended group descriptions and generator values for use in conjunction with the U-Prove Cryptographic Specification V1.1 (Revision 2).